Alternative Approaches to Vibration Measurement Due to the Blasting Operation: A Pilot Study - Stanislav Kepak; Martin Stolarik; Jan Nedoma; Radek Martinek; Jakub Kolarik; Miroslav Pinka (Sensors, 2019)
As the infrastructure grows, space on the surface in the urban area is diminishing, and the view of the builders is increasingly moving underground. Implementation of underground structures, however, presents a number of problems during construction. One of the primary side effects of tunnel excavation is vibration. These vibrations need to be monitored for potential damage to structures on the surface, and this monitoring is an integral part of any such structure. This paper brings an original pilot comparative study of standard seismic instrumentation with experimentally developed fiber-optic interferometric and acoustic systems for the purpose of monitoring vibration caused by the blasting operation. The results presented show that systems operating on physical principles (other than those previously used) have the potential to be an alternative that will replace the existing costly seismic equipment. The paper presents waveform images and frequency spectra from experimental measurements of the dynamic response of the rock environment, due to blasting operation performed shallowly during the tunnel excavation of a sewer collector. In the time and frequency domain, there is, by comparison, significant agreement both in the character of the waveform images (recording length, blasting operation timing) and in the spectra (bandwidth, dominant maxima).